Development of a pigment-based whole-cell biosensor for the analysis of environmental copper. Issue 47 (5th June 2017) - Chen, Pei-Hsuan; Lin, Chieh; Guo, Kai-Hong; Yeh, Yi-Chun
Abstract : A engineered whole-cell biosensor is developed to generate output signals for the environmental copper analysis. Abstract : Using engineered microorganisms to detect heavy metals in the environment has proven to be highly effective and robust. This paper reports on the development of a novel microbial sensor for the detection of copper ions. To develop this microbial sensor, we screened and characterized various biological parts, including promoters, output signals, and hosts. In addition, we used the plant pigment betaxanthin to output fluorescent signals in order to reduce the detection time. The resulting whole-cell biosensor presented a good sensitivity when detecting copper ions in environmental samples including freshwater pond and tap water.